Quality of component crops as influenced by intercropping of canola oilseed rape (Brassica napus) and Ethiopian mustard (Brassica carinata) with Indian rape (Brassica rapa var. Toria) (Journal of Oilseed Brassica, 2026)
A field experiment was conducted at Punjab Agricultural University, Ludhiana during rabi 2014-15 to study the effect of different row proportions and row spacing of component crops in intercropping system on quality of canola oilseed rape (Brassica napus), Ethiopian mustard (Brassica carinata) and Indian rape (Brassica rapa). The experiment comprising, 14 treatments was conducted in randomized complete block design with three replications. Indian rape matured at 94 days after sowing whereas both oilseed rape and Ethiopian mustard matured at 164 days after sowing. Differences in seed oil content in Indian rape and oilseed rape were significant but seed protein content of all crops were non significant. Oil and protein yield of component crops though decreased in intercropping, the total oil yield and protein yield of both canola and non canola oilseed rape were significantly higher than their respective sole crop yields. Total oil and protein yields of Ethiopian mustard sown as sole crop or intercrop were comparable. Fatty acid composition of oil of only oilseed rape was influenced by intercropping.